Differences in the Effectiveness of the Antibacterial Power of Chlorhexidine 0.2% and Povidone Iodine 10% against the Growth of Porphyromonas Gingivalis Bacteria - Dwi Leni Yuliana (Saniya Institute, 2023)
One of the causes of gingivitis and periodontitis is the bacteria Porphyromonas gingivalis. In liquid form, chlorhexidine and povidone iodine are antibacterial and can stop the growth of P. gingivalis bacteria. The goal of this study was to find out how chlorhexidine and povidone iodine liquids were different in their ability to stop the growth of P. gingivalis bacteria. In a lab experiment with a population of P. gingivalis bacteria, a post-test-only group design was used. Seven samples were chosen at random for each treatment, and the samples were split into three groups. The normality test uses the Shapiro-Wilk test, and statistical tests use the independent sample t-test. The results of the independent sample t-test show a p value < 0.05, which indicates that overall there is a significant difference in the antibacterial activity of chlorhexidine solution and povidone iodine solution against the growth of P. gingivalis bacteria, so it can be concluded that administering the povidone iodine solution is more effective than the chlorhexidine solution as an antibacterial against the growth of P. gingivalis bacteria.